2008
DOI: 10.4269/ajtmh.2008.79.864
|View full text |Cite
|
Sign up to set email alerts
|

Cysticercosis of the Breast, a Rare Imaging Finding

Abstract: Parasitic infection of the breast is rare, especially in cases of cysticercosis. This disease is acquired by ingestion of tapeworm eggs in contaminated food and water supplies or from hands improperly washed after a bowel movement. Diagnosis is usually made incidentally. We report a patient with cysticercosis of the breast. The patient was a 63-year-old woman who had no clinical manifestations, but cysticercus was observed to cause calcifications detected by mammography. Computed tomography demonstrated brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…To the best of our knowledge, this is the first confirmed case report of cysticercosis affecting the male breast from a developed country. Similar to the findings in our case, reported histological features of mammary cysticercosis include a three-layered structure with an outer cuticular layer, a middle cellular layer and an inner fibrillar layer with a dense inflammatory reaction in the surrounding stroma which commonly contains histiocytes and eosinophils 6 8. The host manifests an inflammatory reaction once the cyst starts to degenerate, and old cysts in which the parasite has died commonly calcify 2…”
Section: Discussionsupporting
confidence: 88%
“…To the best of our knowledge, this is the first confirmed case report of cysticercosis affecting the male breast from a developed country. Similar to the findings in our case, reported histological features of mammary cysticercosis include a three-layered structure with an outer cuticular layer, a middle cellular layer and an inner fibrillar layer with a dense inflammatory reaction in the surrounding stroma which commonly contains histiocytes and eosinophils 6 8. The host manifests an inflammatory reaction once the cyst starts to degenerate, and old cysts in which the parasite has died commonly calcify 2…”
Section: Discussionsupporting
confidence: 88%
“…There was no specific feature to suggest parasitic infestation in their case (Sinha et al, 2008). Lucarelli et al reported a tubular worm-like appearance suggestive of calcified larvae in the intermuscular area of the pectoral major (Lucarelli et al, 2008). In our case, the architecture of the breast parenchyma was well preserved.…”
Section: Discussionmentioning
confidence: 48%
“…Sending in the patient for mammography is the instinctive next step in establishing a diagnosis. In our patient, mammography showed no distinctive features suggesting cysticercosis, but in a few patients, it can show calcified larvae [9]. High-resolution ultrasound, on the other hand, can be an invaluable tool to diagnose cysticercosis.…”
Section: Discussionmentioning
confidence: 49%